Ghana Library Association Biennual Congress, 2008; Ghana Library Association Seminar and Annual General Meeting, 2009 - Arkorful, Mary Adwoa (Ghana Library Journal, 2011)
This special issue is a compilation of conference papers presented at the GLA Biennial Congress of 2008, and the Seminar and Annual General Meeting of 2009. The theme of the Congress was; “Copyright, Information and Education”. The theme is very relevant because Copyright is a global issue with interventions from relevant international institutions. In Ghana, Copyright is mainly linked to music as such there has been very little or no intervention from librarians. As an institutional member of the International Federation of Libraries and Institutions(IFLA) the Ghana Library Association has made consistent efforts to align its Congress and Seminar themes to those of IFLA.